Brand Image Dan Suku Bunga Kredit Terhadap Peningkatan Nasabah Kredit di PT Bank Negara Indonesia (Persero) Tbk Kantor Cabang Kediri - Nasrudi, Nasrudi; Arisyahidin, Arisyahidin (Otonomi, 2025)
The rapid development of the global market in recent decades has brought significant changes in various industrial sectors including the banking sector. Tight competition in the banking sector encourages companies to carry out creative and innovative marketing in attracting and retaining credit customers. Brand Image and Credit Interest Rates are two elements that are very influential in the competition in the Indonesian banking sector today. Banks strive to strengthen their Brand Image by providing good service. At the same time, they also compete fiercely in offering competitive Credit Interest Rates. This study aims to examine the effect of Brand Image and Credit Interest Rates on increasing credit customers at PT Bank Negara Indonesia (Persero) Tbk Kediri Branch Office. This research method uses Interviews and Questionnaires analyzed with the SPSS V.29 application. The results of the interviews showed that Brand Image and Credit Interest Rates had a significant influence on increasing credit customers. The results of the multiple linear regression test showed an R Square value of 0.652, which means that 65.2% of the variance in Increasing Credit Customers can be explained by the Brand Image and Credit Interest Rate variables, while 34.8% is explained by other variables. At the end of the study, BNI Kediri Branch Office has succeeded in increasing credit customers through effective Brand Image and Credit Interest Rate strategies, with a superior Brand Image based on the CCSL Survey and competitive credit interest rates. A more structured understanding is needed so that credit customers become optimally loyal.